Dance Participation and Attendance in Denmark - Catarina Marv\~ao; Karol Borowiecki (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2015)
Dancing may be one of the most competitive professions available career-wise. The lack of job opportunities and the competitiveness, the inherent expense in costumes and training and the high risk of injuries mean that only few dancers are able to make it their profession. However, dancing is an activity that comes with positive externalities, as various socio-economic benefits are experienced by those who practice dance non-professionally. Despite the importance of dancing, very little is known with respect to the profiles of dancers. This chapter, by availing of an information database on cultural preferences and habits in Denmark for 2004, illustrates the profiles of dancers and dance audiences and so deepens the current knowledge on the functioning of the dance market. We show that there exists a very strong positive correlation between cultural participation and the well-being of a society. These links are carefully described in the chapter.
Keywords: A12; I31; Z11; Z19; 330; Dance; cultural preferences; welfare; competitiveness